MyD88 and TRIF mediate divergent inflammatory and regenerative responses to skeletal muscle ischemia. Issue 5 (20th May 2014) - Sachdev, Ulka; Cui, Xiangdong; Xu, Jia; Xu, Jun; Tzeng, Edith
Abstract We have previously shown that MyD88 KO mice appear protected from ischemic muscle injury while TRIF KO mice exhibit sustained necrosis after femoral artery ligation (FAL). However, our previous data did not differentiate whether the protective effect of absent MyD88 signaling was secondary to attenuated injury after FAL or quicker recovery from the insult. The purpose of this study was to delineate these different possibilities. On the basis of previous findings, we hypothesized that MyD88 signaling promotes enhanced inflammation while TRIF mediates regeneration after skeletal muscle ischemia. Our results show that after FAL, both MyD88 KO mice and TRIF KO mice have evidence of ischemia, as do their control counterparts. However, MyD88 KO mice had lower levels of serum IL‐6 24 h after FAL, while TRIF KO mice demonstrated sustained serum IL‐6 up to 1 week after injury. Additionally, MyD88 KO mice had higher nuclear content and larger myofibers than control animals 1 week after injury. IL‐6 is known to have differential effects in myoblast function, and can inhibit proliferation and differentiation. In tibialis anterior muscle harvested from injured animals, IL‐6 levels were higher and the proliferative marker MyoD was lower in TRIF KO mice by PCR. Furthermore, expression of MyD88 appeared to be higher in skeletal muscle of TRIF KO mice. In vitro, we showed that myoblast differentiation and proliferation were attenuated in response to IL‐6 treatment giving credence to the finding that low IL‐6 in MyD88 KO mice may be responsible for larger myocyte sizes 1 week after FAL. We conclude that MyD88 and TRIF work in concert to mediate a balanced response to ischemic injury.